2022
DOI: 10.3390/metabo12010060
|View full text |Cite
|
Sign up to set email alerts
|

Major Nutritional Metabolic Alterations Influencing the Reproductive System of Postpartum Dairy Cows

Abstract: Early successful conception of postpartum dairy cows is crucial in determining the optimum reproductive efficiency and profitability in modern dairy farming. Due to the inherent high production potential of modern dairy cows, the extra stress burden of peri-parturient events, and associated endocrine and metabolic changes causes negative energy balance (NEBAL) in postpartum cows. The occurrence of NEBAL is associated with excessive fat mobilization in the form of non-esterified fatty acids (NEFAs). The phenome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 207 publications
(258 reference statements)
0
19
0
Order By: Relevance
“…Heat stress causes various adverse modifications at physiological and metabolic level in cows [10,11,38]. Timely conception of cows is imperative for profitable dairy and beef farming.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat stress causes various adverse modifications at physiological and metabolic level in cows [10,11,38]. Timely conception of cows is imperative for profitable dairy and beef farming.…”
Section: Discussionmentioning
confidence: 99%
“…Ambient temperature exceeding 25 °C causes heat stress in mammals including cattle [7,8]. Whereas high temperature in the range of 35 -40 °C causes enormous alterations in physiology and biochemistry of the body [8][9][10][11]. Heat stress associated biochemical changes in the reproduction system of cattle leads to delayed conception and low fertility rates [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, earlier we reported that immediate culture media change after the completion of heat stress induced early cell proliferation when compared to the heat stress group with culture medium change at 48 h post-treatment [ 21 ]. This phenomenon needs further investigation; a preliminary hypothesis may be drawn that heat stress is an energy-intensive process, as supported by our previous review of the literature studies [ 8 , 32 , 33 ]. Acute heat stress accumulated intracellular ROS and caused an increase in apoptosis of granulosa cells; this phenomenon is commonly observed in heat-stressed cells [ 4 , 29 ].…”
Section: Discussionmentioning
confidence: 72%
“…Heat stress has been shown to alter granulosa cell survival, limit cell proliferation transition, decrease hormone synthesis and secretion, cause oxidative stress, and promote apoptotic manifestation [ 3 , 4 , 5 ]. Impairment of granulosa cells (through heat or occupational hazard stress) leads to disruption of ovarian activity and oocyte development competence [ 6 , 7 , 8 ]. Higher ambient temperatures are shown to be associated with decreases in ovarian reserves and reproductive aging [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The early postpartum achievement of conception is imperative for profitable dairy farming. However, postpartum cows can suffer from a negative energy balance, which causes lipolysis of body fat reserves in the form of non-esterified fatty acids [40][41][42]. This phenomenon, when accompanied with low body condition scores, clinical ketosis, decreased feed intake, fatty liver, and other morbidities, leads to impairment of the reproduction process [43][44][45].…”
Section: Discussionmentioning
confidence: 99%